Protocol for "Seal or Varnish?" (SoV) trial: a randomised controlled trial to measure the relative cost and effectiveness of pit and fissure sealants and fluoride varnish in preventing dental decay - Chestnutt Ivor Gordon; Chadwick Barbara Lesley; Hutchings Simon; Playle Rebecca; Pickles Timothy; Lisles Catherine; Kirkby Nigel; Morgan Maria Zeta; Hunter Lindsay; Hodell Ceri; Withers Beverely; Murphy Simon; et al. (BMC, 2012)
Abstract Background Dental caries remains a significant public health problem, prevalence being linked to social and economic deprivation. Occlusal surfaces of first permanent molars are the most susceptible site in the developing permanent dentition. Cochrane reviews have shown pit and fissure sealants (PFS) and fluoride varnish (FV) to be effective over no intervention in preventing caries. However, the comparative cost and effectiveness of these treatments is uncertain. The primary aim of the trial described in this protocol is to compare the clinical effectiveness of PFS and FV in preventing dental caries in first permanent molars in 6-7 year-olds. Secondary aims include: establishing the costs and the relative cost-effectiveness of PFS and FV delivered in a community/school setting; examining the impact of PFS and FV on children and their parents/carers in terms of quality of life/treatment acceptability measures; and examining the implementation of treatment in a community setting. Methods/design The trial design comprises a randomised, assessor-blinded, two-arm, parallel group trial in 6-7 year old schoolchildren. Clinical procedures and assessments will be performed at 66 primary schools, in deprived areas in South Wales. Treatments will be delivered via a mobile dental clinic. In total, 920 children will be recruited (460 per trial arm). At baseline and annually for 36 months dental caries will be recorded using the International Caries Detection and Assessment System (ICDAS) by trained and calibrated dentists. PFS and FV will be applied by trained dental hygienists. The FV will be applied at baseline, 6, 12, 18, 24 and 30 months. The PFS will be applied at baseline and re-examined at 6, 12, 18, 24, and 30 months, and will be re-applied if the existing sealant has become detached/is insufficient. The economic analysis will estimate the costs of providing the PFS versus FV. The process evaluation will assess implementation and acceptability through acceptability scales, a schools questionnaire and interviews with children, parents, dentists, dental nurses and school staff. The primary outcome measure will be the proportion of children developing new caries on any one of up to four treated first permanent molars. Discussion The objectives of this study have been identified by the National Institute for Health Research as one of importance to the National Health Service in the UK. The results of this trial will provide guidance on which of these technologies should be adopted for the prevention of dental decay in the most susceptible tooth-surface in the most at risk children. Trial registrations ISRCTN ref: ISRCTN17029222 EudraCT: 2010-023476-23 UKCRN ref: 9273